Prospecção farmacológica de compostos sintéticos “alkalóides-like” para o tratamento de gliomas malignos - Oliveira, Mona das Neves (2013)
Glioblastomas (GBMs) are the most common and aggressive primary tumors of the CNS. The survival of patients with this diagnosis remains very low, with poor prognosis even after surgical therapy associated with radiotherapy and chemotherapy. The present work carried out a screening for 24 synthetic “alkaloid-like” to determine their effects on cell viability of quimioresistentes human (Gl-15 and U251) glioblastoma cells and murine (C6) glioma cells. Among the alkaloids tested (100μM) RLB87 was the most cytotoxic for transformed cells, inhibiting the viability in 75.0% 97.2% 76.6% of GL-15, U251 and C6 cells, respectively, after 72 h exposure, and it did not show toxicity to normal glial cells. It was also observed that RLB87 promoted apoptosis, 24 and 72 h after treatment, in a time-dependent manner. Moreover RLB87 also inhibited cell migration and proliferation with cells arrest at G0/G1 phase, since 24 h after treatment. Additionally, the cytotoxicity of four RLB87 analogues was tested in view to elucidate important aspects in chemical structure, required for its activity. We observed positive correlation between cytotoxic effect and isomeric of phenyl functions, with ester function and also lipophilicity. These finding suggest the “alkaloid-like” RLB87 as a promising anticancer agent as well as a prototype for new agents for treatment of malignant and recurrent gliomas.